Peer attachment during adolescence and emerging adulthood - Delgado Gallego, Irene; Oliva Delgado, Alfredo; Sánchez Queija, Inmaculada (Anales de Psicología / Annals of Psychology, 2010)
The present research analyzes how peer attachment changes during adolescence and emerging adulthood. The influence of the early affective relationships established between adolescents and their parents and possible differences associated with sex are considered. Using a longitudinal methodology, a sample of 90 adolescents were interviewed at the age of 13, 15, 18 and 22. At the age of 13, they completed the Parental Bonding Instrument of Parker, Tuplin and Brown (1979), which evaluated the adolescents’ memories of their early attachment established with their parents. Also, they completed the Inventory of Peer Attachment of Armsden and Greenberg (1987). Adolescents completed again the last inventory at the age of 15, 18 and 22. Results show that peer attachment increases with time. At the same time, adolescents who remembered a high parental affect demonstrate higher scores in peer attachment than adolescents who remembered low parental affect. The most significant differences are found in early and middle adolescence. These results support the idea of the continuity between affective relations established in these periods of time. Moreover, maternal influence on peer attachment was higher than that of fathers. Related to sex differences, girls demonstrate higher scores in peer attachment compared to boys, although these differences decrease over time.